Sustainable development, e‐learning and Web 3.0: A descriptive literature review. Issue 3 (2014) - ,
Abstract : Purpose – The purpose of this paper is to present a descriptive literature review and a classification scheme for studies on sustainable development, e‐learning and Web 3.0 that contribute toward sustainable e‐learning. The aims are to discover and highlight some ideas on developing a sustainable learning in higher education in Malaysia.Design/methodology/approach – The paper examines the elements of e‐learning, technology, application, sustainable development and teaching and learning principles that contribute toward a sustainable e‐learning through a descriptive literature review approach and a classification scheme.Findings – The findings show that even though sustainable e‐learning research is still limited, contributions to sustainable e‐learning were recognized and some ideas and perspectives for the development of a sustainable e‐learning framework were identified. Furthermore, this paper identified the gaps in the findings; therefore, this paper will try to minimize these gaps through the initial sustainable e‐learning framework.Originality/value – The paper is expected to provide further ideas of developing a sustainable e‐learning framework, as well as the importance of a sustainable e‐learning to provide quality learning through technology, application, sustainable development and teaching and learning principles perspectives.